No Mode of Being, No Mode of Signifying: The Anti-Modist Emptiness Argument in the Destructions of the Modes of Signifying - Crimi, Milo (Vivarium, 2024)
The Destructions of the Modes of Signifying (henceforth: dms) is an anonymous fourteenth-century polemic against modist speculative grammar (grammatica speculativa). Wielding Ockhamist logic and metaphysics, the dms repeatedly attacks the very root of modism: the claim that the grammatical features of language are grounded in the metaphysical properties of the world. I call this the Modist Correspondence Thesis (henceforth: mct). In its most general form, mct says that every mode of signifying exhibited by an utterance corresponds to a mode of being exhibited by a thing. The Emptiness Argument of the dms tries to show that mct fails to accommodate certain special cases, such as privative, fictitious, and divine utterances, like ‘blindness’ (caecitas), ‘chimera’ (chimaera), and ‘deity’ (deitas). The modist Thomas of Erfurt directly addresses the Emptiness Argument, anticipating the anti-modist criticisms present in the dms. In doing so, he points the way to alternative formulations of mct that are immune to those criticisms.